Leadership, Organizational Commitment and Motivation as Mediation of PPNPN Performance - Pudjianto, Muchammad; Ali Iqbal, M.; Badawi Saluy, Ahmad (Dinasti International Journal of Economics, Finance & Accounting, 2021)
This research effort is to determine the performance of non-civil servant government employees at BPPI where the influence of leadership and organizational commitment can provide an explanation for strengthening the influence through motivation. Questionnaires were distributed to emphasize the objectivity of the 43 respondents' statements in a quantitative, descriptive, associative approach. The evaluation of the model was carried out by testing the reflective relationship with partial least squares based on structural equation modeling or PLS-SEM using the SmartPLS statistical application. The results showed that leadership had a positive and significant effect on motivation, but not significantly on performance. However, the role of motivation is able to mediate leadership on performance with a positive and significant effect. Organizational commitment has a positive and significant effect on motivation, and significantly on performance. And the role of motivation is also able to mediate organizational commitment to performance with a positive and significant influence.